2023
DOI: 10.1038/s41594-023-00947-3
|View full text |Cite
|
Sign up to set email alerts
|

A co-transcriptional ribosome assembly checkpoint controls nascent large ribosomal subunit maturation

Abstract: During transcription of eukaryotic ribosomal DNA in the nucleolus, assembly checkpoints exist that guarantee the formation of stable precursors of small and large ribosomal subunits. While the formation of an early large subunit assembly checkpoint precedes the separation of small and large subunit maturation, its mechanism of action and function remain unknown. Here, we report the cryo-electron microscopy structure of the yeast co-transcriptional large ribosomal subunit assembly intermediate that serves as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…DEAD-box DNA/RNA helicases such as DDX21 have been implicated in the removal of aberrant R-loops (DNA/RNA hybrids) during RNA transcription [97][98][99] , but Plasmodium DDX21 has also been implicated with rRNA maturation in ribosome biogenesis 37 . Other RNA-binding proteins that copurified with PfHO, Nop52 and RAP, also show low-level sequence homology to ribosome assembly factors 100,101 . Prokaryotic ribosome assembly is a co-transcriptional process regulated by, and in close proximity to RNA transcriptional machinery [102][103][104] .…”
Section: Discussionmentioning
confidence: 99%
“…DEAD-box DNA/RNA helicases such as DDX21 have been implicated in the removal of aberrant R-loops (DNA/RNA hybrids) during RNA transcription [97][98][99] , but Plasmodium DDX21 has also been implicated with rRNA maturation in ribosome biogenesis 37 . Other RNA-binding proteins that copurified with PfHO, Nop52 and RAP, also show low-level sequence homology to ribosome assembly factors 100,101 . Prokaryotic ribosome assembly is a co-transcriptional process regulated by, and in close proximity to RNA transcriptional machinery [102][103][104] .…”
Section: Discussionmentioning
confidence: 99%
“…The maturation of the 47S pre-rRNA is co-transcriptional and is initiated as soon as the transcript emerges from the Pol I complex by the assembly of ribosome biogenesis factors and ribosomal proteins into a premature ribosomal particle in the nucleolus ( 12 , 98 , 99 ). The earliest stable pre-ribosomal intermediate to form is called the 90S pre-ribosome or small subunit processome (SSU), which comprises >70 assembly factors, including the transcription U three proteins (t-UTPs), the U3 small nucleolar ribonucleoprotein (U3 snoRNP), several small subunit ribosomal proteins and the nascent pre-rRNA transcript.…”
Section: Aberrant Rrna Processing In Cancermentioning
confidence: 99%
“…While this review primarily focuses into the mechanisms and consequences of increased ribosome biogenesis in cancer, the intertwining regulatory mechanisms of ribosome biogenesis and heterogeneity raise questions about their interplay and significance in cancer progression. Given that most rRNA processing and modifications occur concomitantly with transcription, the factors involved likely exhibit tight spatial and temporal coordination with RNA Pol I elongation ( 12 , 98 , 99 ). This implies that changes in RNA Pol I transcription rate could result in alteration in rRNA modification pattern.…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%
“…NOC1 in yeast works as a heterodimer with NOC2 during the initial maturation of the ribosomal RNA (rRNA) and in the transport of the pre-60S ribosomal subunit, a process that is completed by NOC2/NOC3 heterodimers ( Milkereit et al, 2001 ). Studies on the distribution of affinity-tagged NOC1 and, more recently, proteomics and crosslinking coupled to mass spectrometry, confirmed the presence of NOC1 in the early pre-60S complex ( Sailer et al, 2022 ; Dorner et al, 2023 ), while cryo-EM studies showed its role in the formation of heterodimers with NOC2, essential for the quality-control checkpoint of the maturation of the large ribosome subunit ( Sanghai et al, 2023 ).…”
Section: Introductionmentioning
confidence: 96%